2020
DOI: 10.1016/j.ejvs.2020.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous AXillary Artery (PAXA) Access at the First Segment During Fenestrated and Branched Endovascular Aortic Procedures

Abstract: The paper reports anatomical and intra-operative data on the percutaneous use of the axillary artery first segment for upper extremity access during complex endovascular aortic procedures. This prospective study offers new data supporting a technically feasible and relatively safe percutaneous access to deliver bridging stents during endovascular treatment of thoraco-abdominal or complex abdominal aortic aneurysms, increasing the treatment options at physician's disposal.Objective: The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 45 publications
(45 reference statements)
0
8
1
2
Order By: Relevance
“…In the entire cohort, vascular access feasibility (Table 5) alone excluded 48 patients (18%) from potential transfemoral repair: an iliac axis <8.5 mm was present in 46 patients (17%), and 2 patients (1%) had no upper extremity access (bilateral occlusion of the subclavian arteries). 29 An inadequate iliac axis was more frequent in women than men [27 (39%) vs 19 (9%); p<0.001). If the custom-made low-profile t-Branch (18-F sheath outer diameter vs 23-F) were made available off-the-shelf, it would increase the vascular access feasibility from 82% to 94% (91% women vs 95% men, p=0.381).…”
Section: Resultsmentioning
confidence: 99%
“…In the entire cohort, vascular access feasibility (Table 5) alone excluded 48 patients (18%) from potential transfemoral repair: an iliac axis <8.5 mm was present in 46 patients (17%), and 2 patients (1%) had no upper extremity access (bilateral occlusion of the subclavian arteries). 29 An inadequate iliac axis was more frequent in women than men [27 (39%) vs 19 (9%); p<0.001). If the custom-made low-profile t-Branch (18-F sheath outer diameter vs 23-F) were made available off-the-shelf, it would increase the vascular access feasibility from 82% to 94% (91% women vs 95% men, p=0.381).…”
Section: Resultsmentioning
confidence: 99%
“…The rate of overall access complications of 10.2% in our cohort aligns with prior results. 15,17,20,21 In our multicenter cohort, the AA strategy was least frequently used; this might be due to the fact that the surgical approach of the axillary artery can be more challenging and possible access complications include pneumothorax and hemothorax. Although no differences in the overall access complication were seen between the four locations, there were significant more peripheral neuropathies seen after PBA.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%
“…The literature also offers data on percutaneous access of the axillary artery, which has been reported to have a low conversion and reintervention rate, using even larger sheath sizes. 10,20,[25][26][27] However, the above-mentioned meta-analysis by Malgor et al 17 also found percutaneous AA to be inferior to a surgical approach regarding the access complication rate.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%
“…Given the greater number of implanted stent-grafts/materials, it is proposed that this is likely to be more widespread with unclear implications [ 101 ]. Whether the use of a percutaneous approach to the axillary artery will lead to improved clinical outcomes as compared with conventional brachial artery cutdown, or any significant differences exist with use of the right-side upper arm access vs. the left-side approach also remain areas of ongoing research efforts [ 102 , 103 , 104 ]. In addition, many of the perioperative factors discussed in the preceding chapters (such as procedural staging and risk for death during waiting time, optimal patient selection, type of BSs and use of ancillary materials, application of CSFD, or treatment for particular cases, such as post-dissection aneurysms, connective tissue diseases, or failures after prior infrarenal procedures) are only partially understood and represent unmet critical issues needing further study [ 105 , 106 ].…”
Section: Gaps In Knowledge Implications For Practice and Future Direc...mentioning
confidence: 99%